Implementation of madrasa curriculum based on islamic boarding school at al i'tisham wonosari - Eko Ngabdul Shodikin; Rudi Nur Ramadhan; Nurul Hidayat; Fais Maftuch (Yayasan Azhar Amanaa Yogyakarta, 2024)
This study evaluates the effectiveness of curriculum implementation at Madrasah Aliyah Al I’tisham Wonosari, an Islamic boarding school-based institution. The study focuses on the transition from the 2013 Curriculum (K13) to the Independent Curriculum (Kurikulum Merdeka), emphasizing the importance of selecting an appropriate curriculum to enhance educational quality. The research method used is descriptive qualitative, involving 3 educators and 4 students as subjects. Data collection techniques include interviews, observations, and documentation. The results show that Madrasah Aliyah Al I’tisham has implemented K13 for almost ten years with satisfactory effectiveness. However, the transition to the Independent Curriculum faces several challenges, including the need for technical guidance for educators, improvement of facilities, limited access to technology, and the necessity of continuous evaluation and adjustment. Recommendations are provided to address these challenges through intensive training, enhancement of educational facilities, and the development of digital literacy programs. This research is expected to provide guidance for Madrasah Aliyah Al I’tisham in selecting and implementing a more effective curriculum, thereby producing graduates who are well-prepared to face future challenges.